The Importance of the Territorial Articulation of the Intermediate Scale in the Recovery of the Work Memory. The Case of Barbate - Arnet-Callealta, Virginia (Revista de Estudios Andaluces, 2019)
This article explores the recovery of industrial environments to verify the influence that both the coastal landscape and productive activity have on the configuration of the identity image of medium-scale cities. For this, it deepens in the importance of the intermediate scale in the territorial organization to delve into its impact on the articulation of the productive fabric of the seacoast. Subsequently, the methodological application of a contemporary urban recovery instrument is approached, recognizing the specific challenges of the case of study, Barbate, and establishing strategic lines that contribute to respond to the work proposed. Finally, there are a series of thoughts that confirm the development of local identities within the global panorama thanks to the memory of work.